Identiques et différentes – à propos des répétitions dans Madame Bovary - Shiguéhiko Hasumi (Flaubert: Revue Critique et Génétique)
Based on the analysis of an identical sentence (« son père l’amena lui-même ») which has been repeated, under different circumstances and with another meaning, about Charles as well as about Emma, this article has the purpose to measure on several levels the narrative potential of repetitions in Flaubert’s Madame Bovary.